Characterisation of expression and function of respiratory epithelial CD1d - Hajipouran Benam, K (2014)
In this thesis, I examined the expression of CD1d on respiratory epithelial cells (REC) in human and explored its potential role in mucosal immunity in the lungs. Hitherto, there have been no published reports of CD1d expression on REC though it has been observed on other epithelial surface (notably intestinal epithelial cells). This observation, and work in my supervisor’s laboratory demonstrating CD1d-restricted natural killer T cells (iNKT) cells as early players in the lungs of influenza A virus (IAV)–infected mice prompted my interest in this area. I hypothesized that CD1d is expressed on REC and that it contributes to activation of iNKT cells in the lungs via presentation of endogenous or pathogenic glycolipids. I asked following questions – i) is CD1d expressed on REC ii) can this expression be regulated and iii) does CD1d expression on REC have a function. This thesis provides the first evidence for CD1d expression on human RECs (in cell lines and primary RECs) and also presence of alternatively spliced variants. CD1d expression was inducible by viral-associated signals in vitro and despite being non-professional antigen presenting cells, RECs can present glycolipid (α–GC) to, and activate iNKT cells in a CD1d-dependent process resulting in production of both Th1 and Th2 cytokines. Using whole genome expression profiling, I then showed that iNKT cells expressed a distinct profile of genes while in direct contact with α–GC-bound CD1d on RECs compared to cells separated by transwell membrane. Here early biological pathways were dominated by cytokine and chemokine related genes (JAK-STAT signaling pathways, cytokine-responsive elements and cytokine/chemokine genes) and apoptosis-related genes. This suggested that glycolipid-bound CD1d on REC was capable of inducing a programme of immune activation in iNKT cells. I concluded my work by examining if CD1d expression on RECs influenced its active role in immunity. Using wild type and CD1d-deficient transgenic mice challenged with IAV, I showed that CD1d expression is induced on REC in vivo after viral challenge, and in the absence of CD1d, mice showed worse outcome. RECs isolated from CD1d-deficient mice had a much stronger gene expression profile for pro-inflammatory genes. This suggested that CD1d expression on REC could have a bi-directional effect – on the RECs that expressed CD1d (preventing excessive immune-related genes activation) and on the iNKT cells that it engaged (activation, with pro-immunity effects). The thesis concludes with discussion of the potential implications of these findings and future work to examine hypotheses generated from this work.